Eksplorasi Kondisi Culture shock pada Santri Baru di Kota Semarang: Implikasi Terhadap Proses Penyesuaian Diri - Afif Sa’id Ramadhan; Nabila Nova Azzahra; Maulida Hasni Istifadah; Shibilla Anas Tasya; Muslikah Muslikah; Ashari Mahfud (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This article explores the phenomenon of culture shock experienced by new santri in pesantren in Semarang City and its implications for their adjustment process. This research uses a qualitative approach with a narrative study method, involving six new santri who were interviewed about their experiences when they first arrived at the pesantren. The results show that new santri often feel shocked and lonely due to the significant differences in the environment compared to their homes. They face challenges in managing their time, adapting to a busy routine, and interacting with new people. Support from peers and pesantren administrators proved important in helping them overcome culture shock. This article suggests the need for guidance and counseling programs to accelerate the adjustment process of new santri, and emphasizes that this experience can be a valuable lesson for them in facing new environments in the future.